IMPLEMENTASI TECHNOLOGY ACCEPTANCE MODEL DALAM NIAT MEMBELI KEMBALI TIKET BIOSKOP ONLINE - Prianata, Rahadian; Suprapti, Ni Wayan Sri; Suryani, Alit (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this study was to clarify the effect of computer self-efficacy, perceived ease of use, perceived usefulness, and attitudes and repurchase intention on MTix cinema tickets on the site. The population of this study were all people who had purchased cinema tickets using the MTix site and the numbers were not known for certain..The sampling technique in this study with purposive sampling. Indicators research counted 19 indicators with a total of 150 respondents. Data collection techniques in this study using interview and questionnaire. In the questionnaire using Likert scale data measurement scale with five possible answers 1 to 5. Data were analyzed using analysis tools PLS (Partial Least Square). Result is that computer self-efficacy and significant positive effect on the perceived ease of use. Perceived ease of use and significant positive effect on attitudes in buying. Perceived ease of use and significant positive effect on attitudes in buying. Perceived ease of use positive and significant effect on the perception of usefulness and attitude in buying a positive and significant effect on repurchase intention.